IMPORTANCE PERFORMANCE ANALYSIS OF SPORT SHOES PRODUCT ATTRIBUTES IN MANADO (CASE STUDY: ADIDAS SPORT SHOES USER IN MANADO) - Ponomban, Novia A.; Worang, Frederik G.; Pandowo, Merinda H.Ch. (Universitas Sam Ratulangi, 2021)
The competition in the footwear industry as explained earlier shows that this is quite tight due to the number of imported shoe products entering the market, especially China which offers cheaper products. The purpose of this research is to find out the importance and performance of sport shoes attributes. The research sample was 100 users who wear the Adidas Sport Shoes in Manado. The result shows that Convenience, Quality, Durability, Appropriateness, Good fit, and Attractiveness are very importance to consumer compare to others indicators. The followed by Fashion which is relatively importance to consumer, afterwards Easy of Care, Style, Color, price, and the last one Brand Name has the low level of importance in customers mind based on the data plotting. While in term of performance, Quality, Durability, Appropriateness, Good fit, and Attractiveness has a high level of performance compared to the 76 other attributes. They should consider which attributes need to be developed based on the result in quadrant so the consumer will satisfied with the product.Â Keyword: product attributes, importance and performance analysis